The role of HDAC2 in cigarette smoke–induced airway inflammation in a murine model of asthma and the effect of intervention with roxithromycin. (3rd April 2018) - Xia, Mengling; Xu, Hui; Dai, Wei; Zhu, Cong; Wu, Liqin; Yan, Sunshun; Ge, Xiangting; Zhou, Wangfeng; Chen, Cuicui; Dai, Yuanrong
ABSTRACT: Background : Cigarette smoke is well known to worsen asthma symptoms in asthmatic patients and to make them refractory to treatment, but the underling molecular mechanism is unclear. We hypothesized that cigarette smoke can reduce the expression of HDAC2 in asthma and the process was achieved by activating the PI3K-δ/Akt signaling pathway. We further hypothesized that roxithromycin (RXM) can alleviate the impacts by cigarette smoke. Methods : A murine model of asthma induced by ovalbumin (OVA) and cigarette smoke has been established. The infiltration of inflammatory cells and inflammatory factors was examined in this model. Finally, we evaluated the expression of HDAC2, Akt phosphorylation levels, and the effects of RXM treatment on the model described earlier. Results : Cigarette smoke exposure reduced HDAC2 protein expression by enhancing the phosphorylation of Akt in PI3K-δ/Akt signaling pathway. Furthermore, RMX reduced the airway inflammation and improved the level of expression of HDAC2 in the cigarette smoke–exposed asthma mice. Conclusions : This study provides a novel insight into the mechanism of cigarette smoke exposure in asthma and the effects of RXM treatment on this condition. These results may be helpful for treating refractory asthma and emphasizing the need for a smoke-free environment for asthmatic patients.